2010
DOI: 10.1159/000274382
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Lung Acoustic Monitoring Can Help to Differentiate between Various Chest Radiographic Densities in Critically Ill Patients

Abstract: Background: Complementary bedside lung monitoring modalities are often sought in order to assist in the differentiation between several lung opacities in the intensive care unit (ICU). Objectives: To evaluate the use of computerized lung acoustic monitoring as a complementary approach in the differentiation between various chest radiographic densities in critically ill patients. Methods: Lung vibration intensity was assessed in 82 intensive care patients using vibration response imaging. Patients were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 93 publications
0
29
1
2
Order By: Relevance
“…Vibration response imaging (VRI) is a commercially available acoustic lung imaging system that displays breath sound energy distribution as a dynamic grey-scale image [12,13,14,15]. VRI is a noninvasive, radiation-free technique that requires minimal patient effort and can be transported to the bedside [16,17]. We recently reported that the locations of central airway obstructions and the outcomes of procedures could be reliably identified by analyzing the specific patterns of lung images obtained with the use of VRI [18].…”
Section: Introductionmentioning
confidence: 99%
“…Vibration response imaging (VRI) is a commercially available acoustic lung imaging system that displays breath sound energy distribution as a dynamic grey-scale image [12,13,14,15]. VRI is a noninvasive, radiation-free technique that requires minimal patient effort and can be transported to the bedside [16,17]. We recently reported that the locations of central airway obstructions and the outcomes of procedures could be reliably identified by analyzing the specific patterns of lung images obtained with the use of VRI [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tout d'abord, les images obtenues sont des images planaires (comme la radiographie pulmonaire) et non des coupes tomographiques, ce qui fait que la fiabilité de cette technique risque de décroître avec l'hétérogénéité de l'atteinte respiratoire (typiquement importante au cours du SDRA). Par ailleurs, la plupart des études ayant cherché à valider cette technique dans le contexte de l'agression pulmonaire expérimentale ou chez les patients de réanimation sous ventilation mécanique ont utilisé la radiographie pulmonaire comme méthode de référence [40,41], dont les limites sont parfaitement connues [42]. Une seule étude [43] a utilisé le scanner thoracique comme référence pour identifier les phénomènes de recrutement-dérecrutement sur modèle porcin d'agression pulmonaire et a objectivé une excellente corrélation avec l'analyse fréquentielle du signal d'IRV.…”
Section: Imagerie Par Réponse Vibratoire (Irv)unclassified
“…Furthermore, the ability of VRI to evaluate physiological changes and infer clinical response to an intervention has been explored, both in self-ventilating [10,21] and mechanically ventilated patients [16,22]. Naturally, comparisons have been made against ‘gold standard’ imaging technologies (that is, CT) in order to establish levels of sensitivity and specificity [10,15]. Reproducibility of images, intra-rater reliability and inter-rater agreement when interpreting images have also been routes of exploration [11,20].…”
Section: Introductionmentioning
confidence: 99%